PENANGANAN TINDAK PIDANA PEMILIHAN UMUM KEPALA DAERAH BERKAITAN DENGAN PRINSIP NEGARA HUKUM DAN DEMOKRASI - Muhammad Ikhwan Rahman (Jurusan Hukum Ekonomi Syariah Fakultas Syariah dan Hukum Uin Alauddin Makassar, 2019)
AbstractLaw No.10 of 2016 concerning the Election of Governors, Regents and Mayors has included criminal provisions in Chapter XXIV, of course very much more complete when compared to the criminal provisions stipulated in the Criminal Code concerning crimes against carrying out obligations and rights which are classified certain acts, but the Criminal Code is deemed no longer relevant due to the increasingly complex problems in terms of the enforcement of criminal elections and post-conflict local elections. The essence of law enforcement itself can be interpreted as an act of implementing certain legal means to impose legal sanctions to ensure compliance with a rule. So that the mandate of Article 1 paragraph (2) of the 1945 Constitution of the Republic of Indonesia states that